Increased sensitivity of sputum microscopy with sodium hypochlorite concentration technique: A practical experience at RNTCP center - Kaore, Navinchandra M. (Medknow Publications, 2011)
BACKGROUND: In revised national tuberculosis control program (RNTCP), microscopic examination of sputum for AFB plays an important role in the initial diagnosis of tuberculosis. Bacillary concentration after decontamination and liquefaction by 5% sodium hypochlorite is useful in providing increased sensitivity and safety for handling of specimen. MATERIALS AND METHODS: In this cross-sectional, prospective study, carried out at NKP Salve Institute of Medical Sciences and RC, Nagpur, patients were included according to RNTCP criteria. One set of smears was made according to the RNTCP guidelines while another set was prepared by concentration after decontamination with 5% sodium hypochlorite. Both set of smears were stained according to RNTCP method and were screened by two observers separately to remove observer’s bias and graded according to the RNTCP guidelines. A total of 591 sputum samples from 219 patients were included in the study with 168 males (76.71%) and 51 females (23.28%). RESULTS: A total of 77 samples (13.02%) from 34 patients were positive by routine method whereas by concentration method 119 samples (20.13%) from 49 patients were found positive diagnosing 15 additional patients. This rise of 7.11% in sputum positivity over routine is highly significant (P=0.001021, χ(2)=10.78) with 44.11% increase in diagnosed cases. CONCLUSION: There is a statistically significant rise in smear positive cases after concentration with 5% sodium hypochlorite solution. Considering its low cost, decontaminating and liquefaction properties with better sensitivity, this method is safe and can be of vital importance; at least for smear negative cases.